2007
DOI: 10.1177/0961203307079042
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus in a multiethnic US Cohort LUMINA XLVIII: factors predictive of pulmonary damage

Abstract: The objective of this study was to determine the factors predictive of time to the occurrence of pulmonary damage in systemic lupus erythematosus (SLE). Six-hundred and twenty-six SLE patients from a multiethnic (Hispanics, African Americans and Caucasians) longitudinal study of outcome were studied. Pulmonary damage was defined as per the Systemic Lupus International Collaborating Clinics Damage Index. Socioeconomic-demographic, clinical, genetic, serological features, pharmacologic treatments, behavioural, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 53 publications
3
51
0
3
Order By: Relevance
“…The prevalence of resting PAH in CTD is ϳ2.3-10 cases per million (5), typically mostly SSc patients (5-50%) (6)(7)(8)(9)(10)(11)(12), patients with mixed CTD (21-29%) (13), and patients with systemic lupus erythematosus (5-43%) (14)(15)(16). Based on right heart catheterization, the prevalence of resting PAH in SSc is likely 7.9-20% (7,17).…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of resting PAH in CTD is ϳ2.3-10 cases per million (5), typically mostly SSc patients (5-50%) (6)(7)(8)(9)(10)(11)(12), patients with mixed CTD (21-29%) (13), and patients with systemic lupus erythematosus (5-43%) (14)(15)(16). Based on right heart catheterization, the prevalence of resting PAH in SSc is likely 7.9-20% (7,17).…”
Section: Methodsmentioning
confidence: 99%
“…Patients with patient who discontinue sildenafil can decompensate. 18 Increased PA pressure secondary to vasoconstriction and/or small emboli could increase right to left shunting and cause refractory hypoxemia.…”
Section: 13mentioning
confidence: 99%
“…given that auto-antigenicity against U1Ap has been associated with lung disease in SLE and MCTD patients (Nishimaki et al, 1999;Bertoli et al, 2007;Cojocaru et al, 2011;Lian et al, 2012) and has even been shown to be elevated in three different types of lung cancer (Zhang et al, 2005 and2008). Aside from these associations, no study has recorded the predicted accuracy of these correlations and, as a result, chest radiography has been the suggested method to diagnose lung injury (Levitt et al, 2013).…”
Section: Discussionmentioning
confidence: 99%